2020
DOI: 10.3390/nu12041182
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Cooked Black Beans Stimulates a Cluster of Some Clostridia Class Bacteria Decreasing Inflammatory Response and Improving Insulin Sensitivity

Abstract: There is limited information on the effect of black beans (BB) as a source of protein and resistant starch on the intestinal microbiota. The purpose of the present work was to study the effect of cooked black beans with and without high fat and sugar (HF + S) in the diet on body composition, energy expenditure, gut microbiota, short-chain fatty acids, NF-κB, occluding and insulin signaling in a rat model and the area under the curve for glucose, insulin and incretins in healthy subjects. The consumption of BB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…The intraperitoneal glucose tolerance test was determined as previously described 37 administering an intraperitoneal glucose injection according to NIH recommendations 38…”
Section: Intraperitoneal Glucose Tolerance Testmentioning
confidence: 99%
“…The intraperitoneal glucose tolerance test was determined as previously described 37 administering an intraperitoneal glucose injection according to NIH recommendations 38…”
Section: Intraperitoneal Glucose Tolerance Testmentioning
confidence: 99%
“…Interestingly the presence of resistant starch in the whole cooked black bean were more effective to decrease serum triglycerides and total cholesterol, however BPC or WCB significantly decreased total cholesterol and triglycerides in the high fat diet. Due to the low-medium glycemic index of the black bean, 30 the serum glucose and insulin concentration, as well as the glucose tolerance test were similar to the control group, effect that was more evident after the consumption of a high diet. These results could be explained in part due to an increase in fatty acid oxidation particularly in those fed a high fat diet and a decrease in liver lipogenesis.…”
Section: Discussionmentioning
confidence: 77%
“…The decrease in the expression of Cyp7A1 was also in part reinforced by an increase in the protein abundance of FGF15 in the ileum, a protein that is normally synthesized in response to an elevated concentration of intestinal bile acids, 25 however, recent evidence suggest that the gut microbiota can modify the bile acid-FXR-FGF15 axis, and it has been demonstrated that phenolic compounds can interact and modify the gut microbiota. 36 Interestingly, it has been demonstrated lately that a preparation of black bean can selectively modify the gut microbiota, 30 therefore studies are needed to establish a potential interaction between the BPC, the gut microbiota and the mechanism involving FGF15 in order to regulate hepatic cholesterol concentration.…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate the interest of Dr. Cervantes for his/her comments [1] on our article [2] and for providing us with the opportunity to extend the discussion regarding diet composition in our interpretation of the findings of gut microbiota and fecal butyrate concentration. The following is our response to his/her concerns.…”
mentioning
confidence: 99%